2022
DOI: 10.34133/2022/9878957
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Effect of Cation Types on Electrochromic Properties of Titanium Dioxide Nanocrystals

Abstract: Electrochromic (EC) devices have been regarded as promising candidates for energy-saving smart windows, next-generation displays, and wearable electronics. Monovalent ions such as H+- and Li+-based electrolytes are the benchmark insertion ions for EC devices but have serious limitations such as high cost, instability, and difficulty to handle. Seeking multivalent electrolytes is an effective alternative way to prepare high-performance EC devices; unfortunately, the related reports are currently limited to tung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Moreover, it could be possible that Nb, Gd and Er ions in high concentrations block the access to the active layer, as the multivalent ions have a larger size than monovalent Li + . 42 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it could be possible that Nb, Gd and Er ions in high concentrations block the access to the active layer, as the multivalent ions have a larger size than monovalent Li + . 42 …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it could be possible that Nb, Gd and Er ions in high concentrations block the access to the active layer, as the multivalent ions have a larger size than monovalent Li + . 42 The colouration efficiency (CE) is extracted as the slope of the line tting the linear region of the curve of the optical density of (DOD) based on eqn (3). The CE is a crucial parameter in the development of EC devices as it indicates the EC device's optical modulation capability with respect to the intercalation charge density.…”
Section: Electrochemical and Optical Propertiesmentioning
confidence: 99%
“…The superior electrochromic performance of TiO 2 nanocrystals (larger ΔT and improved cycling stability) in Zn 2þ electrolyte was ascribed to the lower potential barriers of Zn 2þ (0.55 eV) in TiO 2 compared to that of Li þ (0.59 eV) and Al 3þ (0.74 eV), showcasing the superiority of multivalent-ion-based ECD than monovalent-ion-based ECDs. [45] Nonetheless, it has been proved that the intercalation energy of ions can be reduced by doping. [37,46] W-doped TiO 2 has reduced Zn 2þ -intercalation energy to 0.86 eV, enabling improved electrochemical performance in W-TiO 2 .…”
Section: Zn 2þ -Insertion-based Multivalent Electrochromismmentioning
confidence: 99%
“…Titanium dioxide (TiO 2 ) is a common material with excellent physical and chemical stability. , Trizio et al found in the preparation of colloidal TiO 2 NCs that Nb 5+ doping can increase the free carrier concentration of TiO 2 NCs and make it produce obvious LSPR absorption in the NIR region. Subsequently, Dahlman et al found in the EC study of Nb-doped TiO 2 NCs that they have the ability to selectively regulate NIR and VIS light.…”
Section: Typical Ncs For Deswsmentioning
confidence: 99%